The philosophy of energy consumption in North Africa, contribution of artificial intelligence - Bourekkadi S.; Hmamouchi S.; El Asri L.; El Amrani O.; Moslih A. (E3S Web of Conferences, 2023)
Some people in North Africa have been accustomed to getting everything, from the consumption of various goods, to luxurious housing, to travel from one country to another, unaware that the necessities of this way of life are very energy intensive. These countries, too, are unaware of the importance and necessity of opening up to each other in order to work together to raise awareness of energy consumption. Through this research, which is based on a scientific approach combining technology, human and social sciences and statistical studies, we have tried to highlight the importance of logical energy consumption while explaining that the consequences will be unexpected in the future in the event of an energy shortage in North Africa.